The vegetable world in Oleksii Dovhiy's poetry - Строкаль, Олександр Миколайович (Київський національний університет імені Тараса Шевченка, 2019)
The article deals with the features of verbalization of the plant world in Oleksii Dovhiy's poetic language. The study found that the natural world for the primitives reflected the entire Universe – its structure, essence, links, which could not be explained or understood by them. That is why all the phenomena and realities of the environment were anthropomorphized. The components of the plant world made up the largest part of conceptual concepts in the worldview of Ukrainians. The language appeared a certain medium for such representations, reflected by the figurative symbolic semantics of the words. Poetry became a special form for representation of these meanings, whereas just in the poetic text the deep symbolism of numerous anthropomorphized images of nature could be shown fully and vividly. In Oleksii Dovhiy's poetic texts realities of the flora are presented quite clearly and multifaceted because a poet is aware of their important role in the Ukrainian cultural tradition. The largest part of these units are presented by trees and their parts. These are the most commonly used lexemes and their derivatives: birch, beech, elm, willow, cherry, pear, oak, guilder rose, maple, poplar, apple tree, etc. Usage of the lexemes with diminutive semantics allows a poet to convey the inner state of the lyrical hero and establish a deeper connection with the reader. Plant world is involved in the creation of feminine and masculine images in the text and in the process of sacralization of a particular locus.

У статті розглядаються особливості вербалізації рослинного світу в поетичній мові Олексія Довгого. Під час дослідження було з’ясовано, що світ природи для первісної людини відображав увесь Всесвіт – його структуру, причиново-наслідкові зв’язки, які вона не могла пояснити чи зрозуміти. Саме тому всі явища та реалії довкілля антропоморфізувалися людиною. Компоненти рослинного світу займали чи не найбільшу частину концептуальних понять у світогляді українців. Мова виступала певним носієм таких уявлень, відображених в образно-символічних значеннях слів. Особливою формою репрезентації цих значень стала поезія, оскільки в поетичному тексті може максимально повно і багатобарвно виявлятися глибокий символізм численних антропоморфізованих образів природи. У поетичних текстах Олексія Довгого реалії рослинного світу представлені досить виразно і багатогранно. Така особливість є цілком закономірною з огляду на їхню вагому роль в українській культурній традиції. Найчисленнішими з-поміж такого типу одиниць є лексеми на позначення дерев та їхніх частин. Спостерігаємо такі найбільш часто використовувані лексеми і їхні похідні: береза, бук, в’яз, верба, вишня, груша, дуб, калина, клен, тополя, яблуня та ін. Уживання поетом лексем зі зменшено-пестливими компонентами дозволяє передавати внутрішній стан ліричного героя та встановлювати із читачем глибший зв’язок. Реалії рослинного світу беруть участь у створенні в тексті жіночих та чоловічих образів та в сакралізації певного локусу.
Рослинний світ у поезії Олексія Довгого
Keywords: tree; florronym; conceptual worldview; Oleksii Dovhiy's poetry; дерево; флоронім; мовна картина світу; поезія Олексія Довгого